COMPARATIVE PERFORMANCE ANALYSIS OF MANUFACTURING COMPANY USING ACCOUNTING-BASED MEASUREMENTS AND MARKET-BASED MEASUREMENTS BETWEEN ISO 9001CERTIFIED AND NOT CERTIFIED COMPANIES - Fardhilla Muhajjir; Hendra Gunawan (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2018)
The purpose of this research is to analyzed the ratio of company performance measured by accounting-based measurementss with ROA and ROE and company performance measured by market-based measurements with MBV and MVA between ISO 9001 certified and non-certified companies in manufacturing sector listed on the Indonesia Stock Exchange during 2014-2016. Data analysis techniques used are different test with Mann-Whitney. The result of the research shows that there are significant differences to the performance of the organization by accounting-based measurements between ISO 9001 certified and non-certified companies. By market-based measurements, there are significant performance differences in the MBV variables but there is no performance difference in the MVA variables between ISO 9001 certified and non certified companies.